Machine learning-based assessment of condylar changes after orthognathic surgery of asymmetric dentofacial deformities - Tang, Jin; Shi, Jiayu; Liu, Shuguang (Frontiers in Surgery, 2025)
IntroductionThis retrospective study aimed to investigate three-dimensional (3D) condyle change including volumetric, positional, rotational alterations in patients with asymmetric dentofacial deformities immediate and long after bimaxillary orthognathic surgery.MethodsThe sample included 36 patients who underwent bimaxillary orthognathic surgery, with a maxillomandibular dental midline deviation >3 mm, excluding those with class II/III malocclusions and craniofacial syndrome. A fully automated deep learning-based assessment method was used to analyze the volume, position and rotation of condyle based on Cone-beam Computed Tomography (CBCT) images. Repeated measures ANOVA was used to compared the changes at three intervals—pre-surgery (T0), one-week post-surgery (T1), and six months post-surgery (T2)—of the deviated sides and non-deviated sides condyle.ResultsThe condyle on the deviated side was smaller than that on the non-deviated side, with significant volume reductions observed six months post-surgery on the deviated side. Several condylar changes were observed immediately after surgery, though of small magnitude, and it mostly tended to return to their original positions 6 months after surgery. However, the condyle rotated laterally on the deviated side and medially on the non-deviated side post operation and in long-term.ConclusionFor patients with asymmetry, condyle on the deviated side undergo greater remodeling than the non-deviated side after orthognathic surgery. There are measurable rotations in the coronal plane of condyle on both sides.